Clinical characteristics of Demodex-associated recurrent hordeola: an observational, comparative study - Sung Yeon Jun (Nature Portfolio, 2021)
Abstract Our study evaluated the association between Demodex infestation and recurrent hordeola and examined the clinical features associated with these eyelid lesions. This was an observational, comparative study. We reviewed 250 patients and divided them into the recurrent hordeolum (n = 153) and control (n = 97) groups. Demodex infestation was detected by epilating eyelashes around the lesion/s and viewing them under a light microscope. Patient medical records and photographs were retrospectively analyzed to identify the clinical characteristics of Demodex-associated recurrent hordeola. Demodex was detected in 91 (59.5%) and 17 (17.5%) patients in the recurrent hordeolum and control groups (p < 0.001), respectively. In the recurrent hordeolum group, Demodex mites were found in 74 (68.5%) and 17 (37.8%) of the adult and pediatric patients (p < 0.001), respectively. Among patients with recurrent hordeola, patients in their 20s were most likely to have concomitant Demodex infestation. Patients with Demodex infestations were also more likely to develop recurrent lesions within a shorter period of time from the primary incision and curettage. The most common presentation of Demodex-associated recurrent lesions was external hordeola (67%) (p = 0.002). Demodex infestation may cause recurrent hordeola in adults and children. These mites may play a greater role in the development of lesions in adult patients. The strongest association between Demodex infestation and recurrent lesions was seen in patients in their 20s. Our results suggest that if the hordeola recur within a short period of time with the clinical characteristics of external location of eyelid, multiple numbers of lesions, or anterior blepharitis, eyelash epilation should be performed to identify the presence of Demodex mites.